2022
DOI: 10.1111/tpj.16019
|View full text |Cite
|
Sign up to set email alerts
|

A stripe rust fungal effector PstSIE1 targets TaSGT1 to facilitate pathogen infection

Abstract: SUMMARY Puccinia striiformis f. sp. tritici (Pst), the causal agent of stripe rust, is a destructive pathogen of Triticum aestivum (wheat), threatening wheat production worldwide. Pst delivers hundreds of effectors to manipulate processes in its hosts during infection. The SGT1 (suppressor of the G2 allele of skp1), RAR1 (required for Mla12 resistance) and HSP90 (heat‐shock protein 90) proteins form a chaperone complex that acts as a core modulator in plant immunity. However, little is known about how Pst effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Although several studies reported cases where pathogen proteins compete with plant proteins for interactions with host proteins 26 28 , no reports of pathogen proteins competing with plant transcription factors to regulate host genes were available. Here, MoSPAB1 competes against rice MYBS1 for the ability to promote Bsr-d1 expression although they may simultaneously bind to the Bsr-d1 promoter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies reported cases where pathogen proteins compete with plant proteins for interactions with host proteins 26 28 , no reports of pathogen proteins competing with plant transcription factors to regulate host genes were available. Here, MoSPAB1 competes against rice MYBS1 for the ability to promote Bsr-d1 expression although they may simultaneously bind to the Bsr-d1 promoter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PstSIE1, an effector lacking any known sequence motifs, was discovered to compete for TaSGT1 binding. Consequently, this disrupted the formation of the TaRAR1–TaSGT1 subcomplex, a chaperone complex that acts as a core modulator in plant immunity, promoting pathogenesis [ 32 ].…”
Section: Plant Pti and Etimentioning
confidence: 99%
“…RNA-seq technology has been widely used in wheat to cope with stress (Ma et al 2021;Zhang et al 2021;Lee et al 2022;Vranic et al 2022). At present, many candidate genes induced by stripe rust have been cloned and preliminarily analysed using RNA-seq, including TaWRKY, TaBCAT1, TaNAC30, TaEIL1, and TaSGT1 (Duan et al 2013;Wang et al 2018;Corredor-Moreno et al 2021;Wang et al 2022;Zhao et al 2022). These results have provided a foundation for further analysis of the interaction between stripe rust and wheat's resistance to rust at the molecular level.…”
Section: Original Papermentioning
confidence: 99%